Basic English For Communication to the Children of Aisyiyah Orphanage in Gorontalo Regency - Indah Wardaty Saud; Nur Halimah; Fadhlan Saini; Adit Pramana Mato (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) IAIN Manado, 2021)
The purpose of learning a foreign language is that participants have language skills: listening, speaking, reading, and writing. However, they often encounter internal and external obstacles in the learning process. External factors can be in the form of a lack of learning media, one of which can be through games. Games are very appropriate to use in learning English. The participants can understand English easily without being forced to learn it. A game is considered good if it can affect the mastery of English and can help students learn English material, which is more than just the activity of playing itself. The problem faced is the lack of knowledge of basic English and English learning models, which is still monotonous in the learning process. The participants in this program were all children from the Asiyiah Limboto orphanage. The Program provided Basic English communication training through games, which began with giving vocabulary using colored and illustrated media, singing, and games. The results achieved in implementing this activity are; increased vocabulary, quickly understanding of English material, added insight, and innovation in teaching English through games.